Financial Bliss : a Couple's Guide to Merging Money Styles and Building a Rich Life Together. (AMACOM Books, 2007)
Holzer provides investment and financial planning services to individuals and families looking for guidance in managing their money. She takes a 'life planning' approach, helping them define financial goals while taking into consideration family, career, retirement, and other life choices. Media-savvy author, Holzer has appeared on the "Today Show", "NBC Nightly News" with Tom Brokaw, "Fox on Money", CNN, CNBC, "Bloomberg", "Lifetime", and local television and radio shows across the country. She has been quoted in such publications as "U.S. News and World Report", "Money Magazine", "Business Week", "Smart Money", "Research Magazine", "Investors Business Daily", "New York Times" and the "Los Angeles Times". Holzer is an Accredited Investment Fiduciary[trademark], a Certified Specialist in Planned Giving, Certified Estate Advisor, and a member of the American Society of Pension Actuaries (ASPA), the National Institute of Pension Administrators (NIPA), the Investment Management Consultants Association (IMCA), and the Western Pension and Benefits Conference Group.